2017
DOI: 10.1073/pnas.1705032114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic principles underlying regulation of the actin cytoskeleton by phosphoinositides

Abstract: The actin cytoskeleton powers membrane deformation during many cellular processes, such as migration, morphogenesis, and endocytosis. Membrane phosphoinositides, especially phosphatidylinositol 4,5-bisphosphate [PI(4,5)P], regulate the activities of many actin-binding proteins (ABPs), including profilin, cofilin, Dia2, N-WASP, ezrin, and moesin, but the underlying molecular mechanisms have remained elusive. Moreover, because of a lack of available methodology, the dynamics of membrane interactions have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 72 publications
8
101
0
Order By: Relevance
“…However, the isolated N-terminal ADF-H domain of twinfilin does not bind lipids with detectable affinity, and also the C-terminal ADF-H domain displays only relatively modest binding to lipids in vitro. These results are consistent with a recent study demonstrating that ADF/cofilins display only transient, low affinity interactions with phosphoinositide-rich membranes (21). Importantly, our experiments revealed that full-length twinfilin binds membranes more strongly compared to ADF/cofilins, and that the C-terminal tail of twinfilin is critical for this high affinity lipidbinding.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the isolated N-terminal ADF-H domain of twinfilin does not bind lipids with detectable affinity, and also the C-terminal ADF-H domain displays only relatively modest binding to lipids in vitro. These results are consistent with a recent study demonstrating that ADF/cofilins display only transient, low affinity interactions with phosphoinositide-rich membranes (21). Importantly, our experiments revealed that full-length twinfilin binds membranes more strongly compared to ADF/cofilins, and that the C-terminal tail of twinfilin is critical for this high affinity lipidbinding.…”
Section: Discussionsupporting
confidence: 93%
“…Our co-sedimentation and DPH anisotropy experiments as well as atomistic simulations demonstrated that, similarly to ADF/cofilins (19,21), twinfilin interacts with negatively-charged phospholipids through electrostatic interactions without penetrating into the hydrophobic acyl chain region of the bilayer. However, the isolated N-terminal ADF-H domain of twinfilin does not bind lipids with detectable affinity, and also the C-terminal ADF-H domain displays only relatively modest binding to lipids in vitro.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Senju et al 380 performed unbiased AA-MD simulations, initiated by placing the protein 0.5 nm above the membrane surface. During the simulations, both proteins interact with the PI(4,5)P 2 -enriched membrane via their large positively charged surface (Fig.…”
Section: Actin-binding Proteins (Abps)mentioning
confidence: 99%